A parametric study of laser spot size and coverage on the laser shock peening induced residual stress in thin aluminium samples. Issue 13 (28th July 2015) - Sticchi, M.; Staron, P.; Sano, Y.; Meixer, M.; Klaus, M.; Rebelo‐Kornmeier, J.; Huber, N.; Kashaev, N.
Abstract : Laser Shock Peening is a fatigue enhancement treatment using laser energy to induce compressive Residual Stresses (RS) in the outer layers of metallic components. This work describes the variations of introduced RS‐field with peen size and coverage for thin metal samples treated with under‐water‐LSP. The specimens under investigation were of aluminium alloy AA2024‐T351, AA2139‐T3, AA7050‐T76 and AA7075‐T6, with thickness 1.9 mm. The RS were measured by using Hole Drilling with Electronic Speckle Pattern Interferometry and X‐ray Diffraction. Of particular interest are the effects of the above mentioned parameters on the zero‐depth value, which gives indication of the amount of RS through the thickness, and on the value of the surface compressive stresses, which indicates the magnitude of induced stresses. A 2D‐axisymmetrical Finite Element model was created for a preliminary estimation of the stress field trend. From experimental results, correlated with numerical and analytical analysis, the following conclusions can be drawn: increasing the spot size the zero‐depth value increases with no significant change of the maximum compressive stress; the increase of coverage leads to significant increase of the compressive stress; thin samples of Al‐alloy with low Hugoniot Elastic Limit (HEL) reveal deeper compression field than alloy with higher HEL value.